Religious scholars (ulama') and political leaders (umara') in the classical Malay texts: A comparative religion approach - Abdul Jalil, Mohd. Noh; Mohd Amin, Wan Mohd Azam (Fakulti Tamadun Islam, Universiti Teknologi Malaysia (UTM), 2017)
This paper aims in analyzing the roles of religious scholars (Ulama’) and political leaders (Umara’) during the Hindu-Buddhist and Islamic periods in the Malay Archipelago. Different roles have been entrusted to the religious authorities by the Malay rulers. During the period of Indian cultural and religious dominance, religious scholars had a special position at the court and played a significant role in maintaining the legitimacy of the king. Close relationship between religious scholars and the Malay rulers is also evident after the coming of Islam to the archipelago. Once again, religious authorities had been entrusted with a special role by the ruling elite. However, the new Muslim scholars took on a significantly different role with regard to functions from that of their Hindu-Buddhist predecessors. Analysis on the roles of both authorities will be made based on evidence found in two classical Malay texts namely the Sejarah Melayu and Bustan al-Salatin. This paper concludes how, after the spread of Islam to the Malay Archipelago relationship between religious scholars and secular leaders changed drastically. Religious scholars (Ulama’) maintained a less direct relationship with political leaders compared to the role of the Brahmin of the devaraja cult. They merely acted as moral advisors to the rulers who would decide whether to accept or to reject religious advice presented to them based on the needs at that time.